[Filming the Curpite dance competitions] - Jasmin Landin::::::photographer::: (2005)
Description supplied by photographer: 'Los camarógrafos filmando las competencias de Los Curpites en la plaza de San Juan Nuevo. Ellos captan los momentos inolvidables de las competencias. Los videos son traídos a Los Estados Unidos para que de esta manera la gente pueda aprender de los acontecimientos en San Juan Nuevo.' - 'A cameraman is filming the Curpite dance competitions in San Juan Nuevo. They captured the special moments on video so we never have to forget who won or lost in the dance competitions. The videos are transported to the United States by San Juaneses who return to Paso Robles. The videos allow people [to] stay connected with the town in the in this way even if they did not have a chance to go to San Juan Nuevo.'